2019
DOI: 10.26434/chemrxiv.7480130.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chasing Aqueous Biphasic Systems from simple salts by exploring the LiTFSI/LiCl/H2O phase diagram

Abstract: <i>Aqueous Biphasic Systems (ABS), in which two aqueous phases with different compositions coexist as separate liquids, have first been reported over a century ago with polymer solutions. Recent observations of ABS forming from concentrated mixtures of inorganic salts and ionic liquids raise the fundamental question of how "different" the components of such mixtures should be for a liquid-liquid phase separation to occur. Here we show that even two monovalent salts sharing a common cation (lithium) but w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, the techniques employed in previous studies, such as NMR, 31,32 Raman, 26−30 and IR spectroscopy, 21,24,25 are only sensitive to the local molecular bonding and orientations and are challenging to capture the whole structure of the forming clusters and aggregates. SAXS provides information about the molecules' size and shape and assemblies from 1 to 150 nm in solution.…”
Section: ■ Water-in-saltmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the techniques employed in previous studies, such as NMR, 31,32 Raman, 26−30 and IR spectroscopy, 21,24,25 are only sensitive to the local molecular bonding and orientations and are challenging to capture the whole structure of the forming clusters and aggregates. SAXS provides information about the molecules' size and shape and assemblies from 1 to 150 nm in solution.…”
Section: ■ Water-in-saltmentioning
confidence: 99%
“…According to previous research, the LE solvation structures may exist at multiple length scales, from a few angstroms to hundreds of nanometers. 17−23 The microscopic structure of different LEs has been investigated via different spectroscopic techniques, such as Fourier transform infrared (FTIR) spectroscopy, 21,24,25 Raman spectroscopy, 26−30 nuclear magnetic resonance (NMR), 31,32 and neutron scattering. 17,20 However, these techniques are only sensitive to the local molecular bonds and orientations, which are the local short-range information (below 1 nm), and it is challenging to capture the information on the middle-range length scale (1− 10 nm) and long-range length scale (above 10 nm).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, when mixing at high concentration lithium bis(trifluoromethane)sulfonimide (LiTFSI) with smaller, more hydrophilic lithium halide salts such as LiCl or LiBr, aqueous biphasic systems (ABS) were obtained. [9][10][11] Beside their interest for separation or recycling, ABS in which two immiscible aqueous phases are formed, one phase being TFSI-rich and the other phase being halide-rich, quickly showed interest for battery application as they enable having distinct aqueous electrolytes and thus distinct chemistries at the positive and at the negative electrodes.…”
Section: Main Textmentioning
confidence: 99%
“…More precisely, past studies have revealed effects of high salt concentrations 7,8,16 on redox potentials for reactions involving cations such as Li + , H + , or Zn 2+ , but our current understanding of the concentration dependence of anion redox is still limited. 17−19 Furthermore, ABS are known for their ability to partition ions, more precisely anions, as previously demonstrated for TFSI [10][11][12]15,16 or for soluble polysulfides. 13 Nevertheless, very little is known regarding solvation properties and speciation of halide anions in ABS.…”
mentioning
confidence: 91%